Overview of recent developments in modelling and simulations for analyses of airspace structures and traffic flows - Zhong, Zhao Wei (2018)
This article discusses the recent developments in modelling and simulations for analyses of airspace structures and traffic flows. The topics discussed are new models/methods proposed by researchers in the world for optimal flight paths/routes, optimal route structures, sectorization and so on and also new developments in the Association of Southeast Asian Nations region. An Association of Southeast Asian Nations modelling and simulation function has been established, so as to perform analyses of airspace structures and traffic flows throughout the Association of Southeast Asian Nations and produce solutions for capacity and efficiency enhancements. The challenges for such research in the Association of Southeast Asian Nations region are also discussed. This review has helped to identify the research gap. The research on air traffic management in the Association of Southeast Asian Nations region is still lacking. Much more efforts should be made in order to meet the demands of this most dynamic and fast growing aviation market in the world. Research on optimal flight paths/routes, more efficient airspace structures and sectorization is expected to be more intensively conducted especially in the Association of Southeast Asian Nations region.